Origin of the dopaminergic innervation of adult neurogenic areas - Höglinger, Günter U.; Arias-Carrión, Oscar; Ipach, Bastian; Oertel, Wolfgang H. (Journal of comparative neurology (1911), 2014)
ABSTRACT Adult neurogenesis, a specific form of brain plasticity in mammals occurring in the subventricular zone (SVZ) and the subgranular zone (SGZ), is subject to complex regulations. Dopamine has been identified as a regulatory factor in rodents, nonhuman primates, and humans. We therefore studied in detail the origin of the dopaminergic innervation to the SVZ and SGZ in rodents. Postmortem anterograde and retrograde tracing combined with immunofluorescence procedures indicate a topographic organization of midbrain dopaminergic projections toward the SVZ. The substantia nigra pars compacta (SNc) projects specifically into the rostral migratory stream, the anterior SVZ, and the dorsal part of the medial and posterior SVZ. In contrast, the ventral tegmental area (VTA) innervates specifically the ventral part of the medial and posterior SVZ. Both VTA and SNc dopaminergic neurons innervate homogenously the lower and upper blade of the dentate gyrus, including the SGZ. Based on these findings, we suggest that the neurogenic areas are in a position to be differentially affected by region‐specific changes in dopamine signaling, the functional implication of which must be further elucidated. J. Comp. Neurol. 522:2336–2348, 2014. © 2014 Wiley Periodicals, Inc. Adult neurogenesis in the mammalian subventricular zone (SVZ), rostral migratory stream (RMS), and subgranular zone (SGZ) is subject to dopaminergic regulation. We provide here the first comprehensive anatomical mapping of their differential innervation by the mesencaphalic dopaminergic cell groups (substantia nigra pars compacta [SNc], ventral tegmental area [VTA], and retrorubral field). The image shows that dopaminergic cells located in the SNc innervate specifically the RMS and the SVZ. The VTA innervates the ventral part of SVZ in the anteroposterior extension. Dopaminergic cells located in the VTA and SNc jointly innervate the SGZ.